2016
DOI: 10.1504/ijbt.2016.077942
|View full text |Cite
|
Sign up to set email alerts
|

Demystification of GM crop costs: releasing late blight resistant potato varieties as public goods in developing countries

Abstract: A few studies have reported some of the costs associated with bringing to market genetically-modified (GM) crops but no comprehensive studies exist on the real cost of the entire process of developing and releasing one GM variety by a not-for-profit institution in a developing country for sustainable agriculture. Despite the lack of documented studies, it is commonly assumed that such an undertaking is cost prohibitive, based on mere hearsay, and on two private sector cost assessments. The present study assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…However, T‐DNA is sometimes inserted only partially or with partial repeats and therefore additional molecular characterization will be needed to confirm the exact number of copies and its integrity. About 50% of the insertions appeared to be single copy, confirming this parameter used in our study on the cost to produce transgenic events (Schiek et al ., ). PCR amplifications were done between the end and the start of contiguous genes as well as between the T‐DNA border sequence and the first gene to avoid amplifying any of the homologs (Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, T‐DNA is sometimes inserted only partially or with partial repeats and therefore additional molecular characterization will be needed to confirm the exact number of copies and its integrity. About 50% of the insertions appeared to be single copy, confirming this parameter used in our study on the cost to produce transgenic events (Schiek et al ., ). PCR amplifications were done between the end and the start of contiguous genes as well as between the T‐DNA border sequence and the first gene to avoid amplifying any of the homologs (Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…Again, here we confirmed that two‐thirds of the transgenic events do not have the vector backbone sequences tested, which is the frequency set by Schiek et al . (). A total of 26 and 15 transgenic events matched our criteria to be selected as candidate lead transgenic events from ‘Desiree’ and ‘Victoria’ respectively (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…Regulatory costs and time associated with the process can vary greatly and depend on the crop, the country, the developer and the inserted genes. Cost estimates for the development of a single GM variety (late blight resistant potato) in a developing country by a not-for-profit institution vary from US$1.4 million to US$1.6 million over 8-9 yr of review (Schiek et al, 2016). In many African countries, genome-edited crops are expected to be regulated through the GM regulatory framework, similarly to the laws in Europe (ISAAA, 2017).…”
Section: Reviewmentioning
confidence: 99%
“…One of the important costs in regulatory dossier development is the toxicity assessment of the new proteins for which the 3R gene technology can build a weight of evidence instead of costly purification, stability, and gavage testing (Habig et al 2018). Therefore, when both projects estimated their regulatory costs, these were found to be reasonable unlike those reported by Refers to products phased out of the market larger players for commodities like maize (Kalaitzandonakes et al 2006;Schiek et al 2016). However, the adoption of biotech potatoes remains challenging due to negative perception by a large part of the public unfamiliar with the challenges and potential solutions to improve agriculture production.…”
Section: Progress Toward Next Generation Of Potato Varietiesmentioning
confidence: 99%